Aerodynamic Characteristics of Ahmed Body with Inverted Airfoil Eppler 423 and Gurney Flap on Fastback Car - Zainal Arifin; Suyitno Suyitno; Dominicus Danardono Dwi Prija Tjahjana; Wibawa Endra Juwana; Rendy Adhi Rachmanto; Chico Hermanu Brillianto; Ubaidillah Ubaidillah; Singgih Dwi Prasetyo; Arinal Falah Muhammad; Mohd Afzanizam Mohd Rosli (Automotive Experiences, 2022)
The installation of aerodynamic devices, such as rear wings with the application of a Gurney flap, is very important to improve the performance of vehicles and can generate downforce and reduce slip when a car turns and brakes. The goal of this study was to determine the aerodynamic characteristics of the addition of a rear wing using an Eppler 423 airfoil, which was applied with a Gurney flap featuring variations in the angle of attack and the height of the Gurney flap. The rear wing was mounted on the Ahmed body with a rear slant angle of 15Â°, which is similar to the configuration on a fastback type car. This research was conducted by 3D modeling through computational fluid dynamics (CFD) simulation using ANSYS Student R18.2 by using ahmed body design. There are three variations in the angle of attack for the rear wing (0Â°, 7.5Â°, and 15Â°), as well as five variations in Gurney flap height of 0%, 0.5%, 1%, 1.5%, and 2% for the chord-line length. In this study, the best variation was found at an angle of attack of 15â° with a height of 2% C. From this configuration improved CL/CD ratio by 25.36% when compared to the results without a Gurney flap.